2022
DOI: 10.3389/fimmu.2022.1023349
|View full text |Cite
|
Sign up to set email alerts
|

A novel risk score based on immune-related genes for hepatocellular carcinoma as a reliable prognostic biomarker and correlated with immune infiltration

Abstract: BackgroundImmunological-related genes (IRGs) play a critical role in the immune microenvironment of tumors. Our study aimed to develop an IRG-based survival prediction model for hepatocellular carcinoma (HCC) patients and to investigate the impact of IRGs on the immune microenvironment.MethodsDifferentially expressed IRGs were obtained from The Genomic Data Commons Data Portal (TCGA) and the immunology database and analysis portal (ImmPort). The univariate Cox regression was used to identify the IRGs linked to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Of note, this IRG signature was able to distinguish high‐risk and low‐risk HCC patients with an AUC of 0.784, 0.720, and 0.697 at 1‐, 3‐, and 5‐year survival, respectively. Additionally, the study found that high‐risk patients had higher levels of Tregs, M0 macrophages, and resting DCs, while low‐risk patients had lower levels of CD8 + T cells, naive B cells, and activated DCs 61 …”
Section: Prognostic Gene Signatures: Focused To Assess the Clinical O...mentioning
confidence: 89%
See 2 more Smart Citations
“…Of note, this IRG signature was able to distinguish high‐risk and low‐risk HCC patients with an AUC of 0.784, 0.720, and 0.697 at 1‐, 3‐, and 5‐year survival, respectively. Additionally, the study found that high‐risk patients had higher levels of Tregs, M0 macrophages, and resting DCs, while low‐risk patients had lower levels of CD8 + T cells, naive B cells, and activated DCs 61 …”
Section: Prognostic Gene Signatures: Focused To Assess the Clinical O...mentioning
confidence: 89%
“…68 Studies have investigated various biomarkers that could impact the prognosis of HCC by regulating apoptosis-related genes. [59][60][61] To this end, a gene signature composed of apoptosis-related genes was examined for its prognostic value in HCC patients. Five differentially expressed apoptosis-related genes, including PPP2R5B, TOP2A, SQSTM1, LGALS3, and BMF, were identified as having prognostic value based on mRNA sequence data from 50 normal tissues and 374 HCC tissues.…”
Section: The Prognostic Value Of the Irgs Signatures In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an urgent need to find new targets for the diagnosis and treatment of liver cancer in the direction of a breakthrough in the current treatment limitations. Some previous studies used TCGA and GEO databases to screen oncogenes and identify prognostic or immune-related genes ( Chen et al, 2020 ; Gao et al, 2021 ; Yan et al, 2021 ; Shen et al, 2022a ; Shen et al, 2022b ; Ding et al, 2022 ; Gao et al, 2022 ; Long et al, 2022 ; Yang et al, 2022 ). However, in this study, four GSE datasets, GSE36376, GSE102079, GSE54236, and GSE45267, were summarized for analysis, hoping to find the mechanism of cancer-promoting and tumor-suppressor factors in liver cancer from the perspective of improving the accuracy of the research results.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, public data and bioinformatic analysis methods have provided us with invaluable resources to find HCC-related oncogenes and tumor-suppressor genes. Some studies searched cancer-related target genes through public databases, whether prognostic oncogene identification ( Gao et al, 2021 ; Yan et al, 2021 ; Shen et al, 2022a ; Gao et al, 2022 ), single-gene research studies ( Ding et al, 2022 ; Yang et al, 2022 ), or immune-related oncogenes ( Chen et al, 2020 ; Shen et al, 2022b ; Long et al, 2022 ), all of which provided a strong basis for targeted therapy and precise treatment of liver cancer. However, many studies only consider the differential expression of oncogenes in tumors, ignoring the important role and potential association of tumor-suppressor genes.…”
Section: Introductionmentioning
confidence: 99%